BRD4 Inhibitor GNE-987 Exerts Anticancer Effects by Targeting Super-Enhancer-Related Gene LYL1 in Acute Myeloid Leukemia. (1st August 2022) - Sang, Xu; Zhang, Yongping; Fang, Fang; Gao, Li; Tao, Yanfang; Li, Xiaolu; Zhang, Zimu; Wang, Jianwei; Tian, Yuanyuan; Li, Zhiheng; Yao, Di; Wu, Yumeng; et al.
Abstract : Background . AML (acute myeloid leukemia) is a common hematological malignancy in children with poor treatment effects and poor prognosis. Recent studies have shown that as a novel BRD4 (bromodomain containing 4) PROTACs (proteolysis targeting chimeras) degrader, GNE-987 can slow down the growth of various tumors and increase apoptosis, with promising clinical prospects. However, the function and molecular mechanism of GNE-987 in AML remain unclear. This study is aimed at investigating the therapeutic effect of GNE-987 on AML and its underlying mechanism. Methods . The association between BRD4 and AML was assessed by studying public databases. After GNE-987 was added to AML cells, cell proliferation slowed down, the cycle was disturbed, and apoptosis increased. Western blotting was used to detect BRD2 (bromodomain containing 2), BRD3 (bromodomain containing 3), BRD4, and PARP (poly ADP-ribose polymerase) proteins. The effect of GNE-987 on AML cells was analyzed in vivo. RNA-seq (RNA sequencing) and ChIP-seq (chromatin immunoprecipitation sequencing) validated the function and molecular pathways of GNE-987 in processing AML. Results . BRD4 expression was significantly elevated in pediatric AML samples compared with healthy donors. GNE-987 inhibited AML cell proliferation by inhibiting the cell cycle and inducing apoptosis. BRD2, BRD3, and BRD4 were consistent with decreased VHL (Von Hippel Lindau) expression in AML cells. In an AML xenograft model, GNE-987 significantly reduced the hepatosplenic infiltration of leukemia cells and increased the mouse survival time. Based on analysis of RNA-seq and ChIP-seq analyses, GNE-987 could target multiple SE- (super-enhancer-) related genes, including LYL1 (lymphoblastic leukemia 1), to inhibit AML. Conclusions . GNE-987 had strong antitumor activity in AML. GNE-987 could effectively inhibit the expression of SE-related oncogenes including LYL1 in AML. Our results suggested that GNE-987 had broad prospects in the treatment of AML.